Relaxation mechanism of rotational type in fracture of weld joints for austenic steels; Theoretical and Applied Fracture Mechanics; Vol. 29, iss. 2, June - Panin V. E. Viktor Evgenyevich; Pleshanov V. S.; Kobzeva S. A.; Burkova S. P. (1998, 1998)
Studied is the mesoscale behavior of plastic deformation and fracture of weld joints for austenic steels. Large-scale rotational modes of deformation in heat affected zones are identified with the first stage of formation of band structures; it is related to the "traveling neck" phenomenon in the base metal. The second stage is connected with crack generation and the state of affairs in the heart-affected zone